2002
DOI: 10.1046/j.1570-7458.2002.00922.x
|View full text |Cite
|
Sign up to set email alerts
|

Induced resistance by Myzus persicae in the peach cultivar ‘Rubira’

Abstract: The effect of a previous infestation by the green peach aphid Myzus persicae (Sulzer) on the settling behaviour and reproduction of the same aphid species was investigated in the resistant peach cultivar Rubira, and compared with that observed in the susceptible control cultivar GF305. A previous infestation of 48 h triggered induced resistance in Rubira. There were significantly fewer aphids settling on preinfested than on uninfested plants, indicating an increased rejection of Rubira as a host plant. The lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
67
0
2

Year Published

2002
2002
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(72 citation statements)
references
References 26 publications
3
67
0
2
Order By: Relevance
“…Moreover, on leaves previously infested by heterospecific aphids, the number of probes and total duration of the pathway increased significantly. These are typical features of the behaviour of aphids feeding on resistant plants, as reported in EPG studies on aphid/plant systems (Campbell et al, 1982;van Helden & Tjallingii, 1993;Cole, 1994;Caillaud et al, 1995;Klingler et al, 1998;Ramirez & Niemeyer, 1999;Sauge et al, 2002). The modifications observed in the feeding behaviour of M. persicae tested on healthy leaves of previously infested potato plants led us to hypothesize that a mechanism of systemic resistance is induced by M. persicae and Ma.…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…Moreover, on leaves previously infested by heterospecific aphids, the number of probes and total duration of the pathway increased significantly. These are typical features of the behaviour of aphids feeding on resistant plants, as reported in EPG studies on aphid/plant systems (Campbell et al, 1982;van Helden & Tjallingii, 1993;Cole, 1994;Caillaud et al, 1995;Klingler et al, 1998;Ramirez & Niemeyer, 1999;Sauge et al, 2002). The modifications observed in the feeding behaviour of M. persicae tested on healthy leaves of previously infested potato plants led us to hypothesize that a mechanism of systemic resistance is induced by M. persicae and Ma.…”
Section: Discussionsupporting
confidence: 60%
“…In Arabidopsis , Moran & Thompson (2001) demonstrated that infestations by M. persicae induced the transcription of PR and β -1,3-glucanase (BGL2) genes, both associated with salicylic acid-dependent responses to pathogens. Such induced resistance to aphids has already been shown by EPG data in the peach cultivar 'Rubira' infested by M. persicae (Sauge et al, 2002) and in one genotype of Medicago truncatula infested by Acyrthosiphon kondoi (Klingler et al, 2005).…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…However, phloem-specific resistance similar to that of AKR has been reported for several aphid-plant interactions, some of which are mediated by a single dominant gene (van Helden and Tjallingii, 1993;Chen et al, 1997;Klingler et al, 1998;Kaloshian et al, 2000). Sauge et al (2002) tested the effect of prior infestation on feeding behavior of Myzus persicae on a resistant genotype of peach (Prunus persicae), in which resistance is also conditioned by a single, dominant gene . As in our study, they observed a significant reduction in phloem sap ingestion on the preinfested, resistant cultivar.…”
Section: Discussionmentioning
confidence: 99%
“…Outliers are plotted as asterisks and circles essential and other amino acids; however, this effect was shown to be species-specific; feeding by S. graminum and Diuraphis noxia Mordvilko increased the nutritional quality of the phloem sap, whereas feeding by R. padi did not. Enhanced susceptibility was also found for a susceptible tomato cultivar after pre-infestation of M. persicae (Civolani et al 2010) and susceptible potato and peach varieties after conspecific pre-infestation of M. persicae or of M. euphorbiae (Dugravot et al 2007;Sauge et al 2002). However, on potato plants, these effects were only observed on previously infested leaves; systemic leaves showed a decrease in susceptibility, suggesting a systemicinduced resistance triggered by pre-infestation (Dugravot et al 2007).…”
Section: Discussion Living In a Groupmentioning
confidence: 83%